correspSearch – Connecting Scholarly Editions of Letters - Stefan Dumont (Journal of the Text Encoding Initiative)
The web service correspSearch collects correspondence metadata from diverse scholarly editions by using the TEI XML–based “Correspondence Metadata Interchange Format” developed by the TEI Correspondence SIG. The web service provides the aggregated data not only on a website, but also via an API in different machine-readable formats and under a free license. The API also makes it possible to automatically refer or even link a letter in one digital edition to related letters provided by other editions. Collecting edited letters in correspSearch and linking them via the API helps overcome certain methodological disadvantages of scholarly editions of letters, since it enables the contextualization and connection of single letters within an entire correspondence network.